Randomized community trial on nosocomial infection control educatinal module for nurses in public hospitals in Yemen: a study protocol - Alrubaiee, Gamil Ghaleb; Baharom, Anisah; Ibrahim, Faisal; Kadir Shahar, Hayati; Mohd Daud, Shaffe; Omer Basaleem, Huda (BMC, 2019)
Background: Nosocomial infections remain a global health problem and they are considered as one of the leading causes of increased morbidity and mortality. In-service training courses related to infection control measures can help nurses to make informed and therapeutic decisions which could prevent or reduce the incidence of nosocomial infections. This study protocol is of a hospital-based trial to develop, implement and evaluate an educational module on nosocomial infection control among nurses in public hospitals in Yemen. This study is currently ongoing and at the analysis stage. Methods: A three-arm single-blinded randomized community hospital-based trial was conducted to evaluate the effectiveness of a newly developed nosocomial infection control educational module among nurses in public hospitals in Yemen. To ensure effective delivery and acquisition of knowledge, the Situated Learning Theory was applied during the course of the intervention. A total of 540 Yemeni in-ward nurses, who had three years nursing diploma and at least a year of working experience in the selected public hospitals were recruited in this study. The hospitals were the unit of randomization whereby eight hospitals were assigned randomly to intervention and waitlist groups. Intervention group-1 (n = 180) received an educational module supported by audio-video CD and a training course for eight weeks. Intervention group-2 (n = 180) was given only the educational module with audio-video CD (without the training course). The waitlist group received no intervention during the period of data collection but they will be given the same training and learning materials after the completion of the study. Discussion: This study contributes to the lack of a nosocomial infection control educational module for nurses in Yemen. It is hoped that the educational module will serve as an effective approach to increase the nurses’ knowledge and improve their practices regarding nosocomial infection control measures and hence decrease the prevalence of nosocomial infections in the future.